On periodic solutions of the equation of a nonlinear oscillator with pulse influence - Samoilenko, A. M.; Samoilenko, V. G.; Sobchuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We study periodic solutions and the behavior of phase trajectories of the differential equation of a nonlinear oscillator with pulse influence at unfixed moments of time.